KEINDAHAN DAN ORNAMENTASI DALAM PERSPEKTIF ARSITEKTUR ISLAM - Atik Hosiah, Yulia Eka Putrie, (Journal of Islamic Architecture, 2012)
This study discusses about the Islamic view from al-Quran and al-Hadith about beauty and its application in the form of architectural ornamentation of the building. This is done to obtain the basic philosophical as well as corridors for the implementation of the beauty in the building, as well as to restore the function of ornamentation itself. Of this study obtained an understanding that displayed beauty should still consider the values of Islam, namely the value of the benefit, harm avoidance, tauhid, cleanliness, and so forth. Between the harm to be avoided in the ornamentation of the mosque is a tendency to exaggerate (mubadzir), depiction of animate beings, disturbance of concentration, intention to brag, luxury, causing difficulty in maintaining cleanliness in the future, and so forth. The expression of beauty can also be done through simplicity, moderation, harmony with nature, concern for human needs and society, and conformity with the rules set by God Almighty and His Messenger. Â  Keywords:Â  Ornamentation, mosque, islamic architecture, beauty